(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Process management as an interdisciplinary field is developing rapidly, driven by its close relationship with information technology and artificial intelligence solutions for process automation and optimization. The increasing number of scientific publications on process management demonstrates its relevance across various fields, including social sciences, medicine, environmental sciences and others. In the context of public administrations, process management serves as a crucial tool for enhancing efficiency, transparency and service quality while ensuring an innovative management approach. This study aims to identify and summarise the potential benefits of implementing process management in public administrations, as presented in scientific articles, by employing theoretical research methods: the deconstruction method, the descriptive method and the synthesis-analysis method. The significance of this research lies in the increasing necessity for public administrations to enhance their adaptability to dynamic, socio-economic and technological challenges by delivering more efficient, data-driven services tailored to citizens’ needs. The findings of this study indicate that the adoption of process management in public administrations can yield over 20 distinct benefits, encompassing both economic and social dimensions thus not only enhancing the operational efficiency of public administration institutions but also contributing to sustainable, innovative and results-oriented governance.